MULTIAGENT APPLICATIONS FOR THE E-LEARNING ENVIRONMENT - Sergey I. Rodzin; Lada S. Rodzina (Открытое образование (Москва), 2016)
The article presents the results of a study on the design of tools to support multi-agent applications for the e-learning. The algorithm of agents conducting negotiations is developed. We analyze the characteristics of a software implementation of the multi- platform agents on JADE. We present minutes of the interaction of agents in the environment e-learning. The results of the experiments outlined areas for further research are the following: the personalization and adaptation of e-learning content to the needs of a particular user, and multi-agent system intellectualization.